Effect of Enzymatic Hydrolysis Time on the Structure and Emulsifying Properties of Soybean Meal Hydrolysate and Preparation and Characterization of Highly Stable Emulsions Stabilized with It - LIU Jingbo, LI Zihao, WEN Hedi, LÜ Siwen, YU Yiding, ZHANG Ting (Shipin Kexue)
In this study, soybean meal was hydrolyzed with alkaline protease. The effect of hydrolysis time on the structure, physicochemical properties and emulsifying properties of soybean meal peptides was investigated. Furthermore, a highly stabile oil-in-water (O/W) emulsion was prepared by using soybean meal peptides with the best emulsification properties. The results showed that as enzymatic hydrolysis progressed, the degree of hydrolysis (DH) gradually increased, and the emulsifying properties of soybean meal hydrolysate first increased and then decreased, reaching the maximum value at 2 h. The emulsion stability gradually decreased. With increasing of DH, the structure of soybean meal peptides gradually unfolded. The content of free amino groups in soybean meal hydrolysate increased, the content of total sulfhydryl groups changed, the surface hydrophobicity decreased, and the secondary structure changed from α-helix to random coil. The optimal process conditions were determined as 40 mg/mL, 0.1 and 8.0 for addition level of soybean meal hydrolysate, oil/water ratio and pH, respectively. The soybean meal hydrolysate adsorbed on the surface of oil droplets could act as a “protective layer”, resulting in good emulsion stability. This study provides new ideas for improving the emulsifying properties of soybean meal protein and also provides a theoretical basis for the development and application of soybean meal peptides in emulsion.